2019
DOI: 10.1186/s12916-019-1338-1
|View full text |Cite
|
Sign up to set email alerts
|

A rapid research needs appraisal methodology to identify evidence gaps to inform clinical research priorities in response to outbreaks—results from the Lassa fever pilot

Abstract: Background Infectious disease epidemics are a constant threat, and while we can strengthen preparedness in advance, inevitably, we will sometimes be caught unaware by novel outbreaks. To address the challenge of rapidly identifying clinical research priorities in those circumstances, we developed and piloted a protocol for carrying out a systematic, rapid research needs appraisal (RRNA) of existing evidence within 5 days in response to outbreaks globally, with the aim to inform clinical research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 109 publications
0
10
0
1
Order By: Relevance
“…This should include a flexible tiered approach, with recommendations tailored to different resourced health systems, enabling sites to switch between tiers as resources becomes available or depleted. Local prioritisation processes in the form of rapid research needs appraisals could also identify key contextual areas to update 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…This should include a flexible tiered approach, with recommendations tailored to different resourced health systems, enabling sites to switch between tiers as resources becomes available or depleted. Local prioritisation processes in the form of rapid research needs appraisals could also identify key contextual areas to update 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current reports of virus transmission from asymptomatic individuals (Zheming et al, 2020). Infectious disease epidemics are a constant threat to everyone (Sigfrid et al, 2019). On July 24, 2020, WHO has reported more than 15 million confirmed COVID-19 cases and had over 600,000 deaths worldwide (World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, epidemiological data from zoonotic viruses such as LASV in humans and animals are crucial in guiding common responses to this health threat. Furthermore, a recent study reported that the detection rate of the LASV in asymptomatic individuals and the identification of populations at high risk were at crucial importance [ 21 ]. We explored both the case fatality rate of the LASV in various category of human populations and the prevalence of LASV in humans, rodents and others mammals.…”
Section: Introductionmentioning
confidence: 99%